Outbreak Caused by Enterobacteriaceae Harboring NDM-1 Metallo-β-Lactamase Carried in an IncFII Plasmid in a Tertiary Care Hospital in Mexico City - Torres-González, Pedro (Antimicrob Agents Chemother, 2015)
Carbapenem-resistant Enterobacteriaceae carrying New Delhi metallo-β-lactamase 1 (NDM-1) have rarely been reported in Latin America. We report of an outbreak caused by a bla(NDM-1)-harboring plasmid spread through different bacterial species, including Escherichia coli (ST617) and Enterobacter cloacae (ST182) isolates from the same patient and three Klebsiella pneumoniae isolates (ST22) derived from three epidemiologically related patients. IncFII plasmids were found in all strains. Measures to control the outbreak were applied successfully.